2018
DOI: 10.1111/sjop.12436
|View full text |Cite
|
Sign up to set email alerts
|

Examining the visual processing patterns of lonely adults

Abstract: Prior research has shown that loneliness is associated with hypervigilance to social threats, with eye-tracking research showing lonely people display a specific attentional bias when viewing social rejection and social exclusion video footage (Bangee, Harris, Bridges, Rotenberg & Qualter, 2014; Qualter, Rotenberg, Barrett et al., 2013). The current study uses eye-tracker methodology to examine whether that attentional bias extends to negative emotional faces and negative social non-rejecting stimuli, or wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Both limited social stimulation and weakening social reflection capacities relate to the sense of loneliness in complex and important ways [13]. Once lonely, bias for negative information processing of cues from others hinders social rehabilitation in a downward cycle [4,183]. Many recent studies have corroborated the corpus of empirical evidence that feelings of loneliness escalate the risk of certain neurological diseases in later life, especially Alzheimer's disease [49].…”
Section: Box 3 Loneliness and Aging In Human Adultsmentioning
confidence: 96%
“…Both limited social stimulation and weakening social reflection capacities relate to the sense of loneliness in complex and important ways [13]. Once lonely, bias for negative information processing of cues from others hinders social rehabilitation in a downward cycle [4,183]. Many recent studies have corroborated the corpus of empirical evidence that feelings of loneliness escalate the risk of certain neurological diseases in later life, especially Alzheimer's disease [49].…”
Section: Box 3 Loneliness and Aging In Human Adultsmentioning
confidence: 96%
“…The Hypervigilance to Social Threat hypothesis proposes that loneliness activates the hypothalamic–pituitary–adrenal (HPA) axis (Bangee, Harris, Bridges, Rotenberg, & Qualter, 2014 ; Qualter et al., 2013 ). For lonely individuals, this hypervigilance is specifically for identifying and attending to social threats whereby they are predisposed to interpret ambiguous social stimuli as threatening (Bangee & Qualter, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is the negative experience of a discrepancy between the desired and achieved personal network of relationships (Maner et al, 2007;de Jong Gierveld et al, 2016) and is related to negative emotional experiences (Hawkley and Cacioppo, 2010). Many studies have demonstrated that loneliness increases attention to social information, especially social threads, using various experimental methodologies such as electroencephalogram (Cacioppo et al, 2015(Cacioppo et al, , 2016 and eyetracking (Bangee et al, 2014). Additionally, it is known that loneliness causes hypervigilance to visual cues about social information (e.g., Bangee et al, 2014) as well as auditory cues about social information (i.e., voice, Shin and Kim, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that loneliness increases attention to social information, especially social threads, using various experimental methodologies such as electroencephalogram (Cacioppo et al, 2015(Cacioppo et al, , 2016 and eyetracking (Bangee et al, 2014). Additionally, it is known that loneliness causes hypervigilance to visual cues about social information (e.g., Bangee et al, 2014) as well as auditory cues about social information (i.e., voice, Shin and Kim, 2019). Although it seems obvious that loneliness increases attention to social stimuli, the effects of loneliness on automatic visual attention to social information remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation